Social determinants of health and rehabilitation service areas: an urban and rural mediation analysis - Nam, Sanghun; Schmidt, Susanne; Dean, Julianna M.; Bokov, Alex F.; Reistetter, Timothy A. (Frontiers in Public Health, 2025)
IntroductionSocial determinants of health significantly shape community discharge (CD) rates in post-acute rehabilitation settings. Additionally, healthcare disparities between urban and rural regions in the United States can affect these discharge rates. These disparities underscore the critical need to understand how social, economic, educational, and healthcare-related factors influence community discharge outcomes to guide equitable healthcare strategies.MethodsThis observational, cross-sectional study analyzed 40,476 ZIP code tabulation area (ZCTA)-level data points linked to rehabilitation service areas and Agency for Healthcare Research and Quality datasets. Exploratory and confirmatory factor analyses identified five social determinants of health domains—social, economic, educational, physical infrastructure, and healthcare—which were assessed using structural equation modeling to evaluate their direct and mediated effects on community discharge rates.ResultsSignificant disparities in community discharge rates were observed across urban and rural areas. Urban areas exhibited lower community discharge rates, influenced by higher social and economic deprivation and limited English proficiency. Conversely, rural areas demonstrated higher rates, attributed to areal social, economic, and education characteristics. Key factors affecting community discharge outcomes included economic inequities, limited healthcare access, and transportation barriers.ConclusionTargeted interventions addressing economic inequities, healthcare access, and transportation challenges are essential to improving community discharge outcomes. These findings inform policy and healthcare practices aimed at fostering equitable rehabilitation services and optimizing community reintegration.